TATA KELOLA PEMERINTAHAN DESA PASCA IMPLEMENTASI UNDANG-UNDANG DESA - DEDEN SUHENDAR (NEO POLITEA, 2020)
Although the village has been given authority by the Village Law to conduct its own affairs, in practice most of the villages studied still tend to depend on the district government. Related to the implementation of village democracy, the space for citizen articulation has not yet been functioned optimally. BPD, as a vehicle for the representation of citizens has not played an optimal role, and there is no effort to strengthen these roles, both from the BPD itself and by residents. So that it can be said that village governance after the implementation of the Village Law can be said to have not experienced much change. The village's authority to form Perdes is also not fully utilized. Not many perdes have been issued, other than major perdes such as the APBDes. With full authority, more perdes should be issued because the consequences will be that many matters will be managed by the village itself. The mindset of the village head seems to have shown something positive, in the sense that the village head has begun to open up democratic space, but nevertheless it takes courage to run it without the need for fears of intervention from the district government. The low quality of democracy has an impact on the performance of village governments. Government performance is only understood as physical development performance. Voices from residents regarding other development needs besides physical development are still not accommodated. In the Sarinagen case, the development carried out was more likely because of the will and initiative of the village head. Even though it still refers to the will of the people conveyed in the Musdes, the portion is not significant.